The Effect of Changing Work Environment on Work-Life Balance and Well-Being of Female Employees During the Covid-19 Pandemic - Uçel, Ela Burcu; Sürgevil Dalkılıç, Olca; Özdamar Ertekin, Zeynep; Oflaç, Bengü (International Journal of Contemporary Economics and Administrative Sciences, 2022)
This study aims to understand how working from home, which started to be implemented due to the Covid-19 pandemic, affects the work-life balance and well-being of female employees. For this purpose, qualitative research method was preferred in order to understand the experiences, thoughts and feelings of working women about flexible working models. In-depth interviews were conducted with 16 female employees between the ages of 29-48. Three main themes emerged as a result of the coding and analysis of the interviews: (I) The effect of the pandemic on perception of work time, (II) Pandemic and changing perception of workplace, (III) Pandemic and work-life balance, (IV) Pandemic and well-being/wellness. The findings of the study will be effective in understanding the hybrid working system, which is expected to continue after Covid-19, and in shaping the human resources policies and practices in the future.